MAKNA EKSISTENSI LEUIT, SAUNG LISUNG, DAN GOAH DI SUNDA KASEPUHAN CIPTAGELAR DALAM MENJAGA KETAHANAN PANGAN - Afina Nisa Aulia; Gregorius Prasetyo Adhitama (Universitas Mercu Buana, 2021)
The traditional Sunda Kasepuhan Ciptagelar community is considered to have achieved food independence because each citizen has sufficient food supplies for the next few years. This community has rules related to food processing, such as storing rice in leuit (barn), pounding rice in saung lisung, and cooking rice in goah (cooking area) according to the teachings of their ancestors (tatali paranti karuhun) and the rules that bind them (tilu sapamilu). The purpose of this study was to see the relationship between the use of leuit, saung lisung, and goah by the community with their success in managing food. So this study is an ethnographic study using qualitative methods with data obtained from field observations, interviews with indigenous experts and local residents, and literature data. The data were analyzed using the theory of the meaning of the environment and architecture of Amos Rapoport, where understanding the meaning of the environment is important so that the physical environment such as buildings can be identified functionally, the value and meaning of their existence. This theory is supported by Edward Relph's theory of space and distance, which states that space has a unique quality where space is able to